Optical coherence tomography angiography vessel density changes after acute intraocular pressure elevation - Zhang, Qi; Jonas, Jost B. (Scientific reports, 2018)
To investigate changes in retinal vessel density in optic nerve head (ONH) and macula after acute intraocular pressure (IOP) elevation, we conducted a prospective observational study. Eyes with IOP rise ≥5 mmHg after 2-hour dark room prone provocative test (DRPPT) were included. Vasculature of ONH and macula was examined by optical coherence tomography angiography (OCTA) at baseline and after DRPPT. Among the 65 eyes of 42 individuals, 40 eyes with qualified images were enrolled. Mean IOP rise was 9.6 ± 4.2 mmHg (5.0-23.3 mmHg) after DRPPT. Retinal vessel density did not differ after IOP rise for either the papillary region (optic nerve head and radial peripapillary capillary layer) or the macula region (superficial, deep and outer retinal layer) (P > 0.05). Vessel density in each subregion did not change either. If only enrolled eyes with IOP rise ≥10 mmHg, similar results were obtained in condition of IOP increase by 15.0 ± 3.6 mmHg. To conclude, eyes with an acute IOP elevation by 10 or 15 mmHg for two hours, while the blood pressure remained constant, the vessel density in both ONH and macula region examined by OCTA did not show significant changes. The observations fit with an IOP-related autoregulation in retinal blood flow for a moderate elevation of IOP.
Gesehen am 02.09.2020